Determining Values of Some Optical Constants for Some Colorants - Soory A. Daher (College of Education for Pure Sciences, 2012)
ABSTRACT For different dyes like methyl green, methyl orange, methyl red, malachite green, crystal violate, safranin, and methylene blue. We calculated their optical constants like wavelengths of maximum absorption, molar extinction coefficient (molar absorptivity), band width, mass attenuation coefficient, cut on and cut off wavelengths and absorption cross section which are very important in manufacturing the optical filters from these dyes. The calculated results are in good agreement with those values calculated by some specialist companies producing optical filters.